Financial Inclusion and Its Dependence on Banking Services in Uzbekistan - Absamatovich Umarov, Zafar; Yashinovna Babaeva, Guzal; Abdugafarovna Ganieva, Umida (International Journal of Psychosocial Rehabilitation, 2020)
This study compared given data of the banking system in the Republic of Uzbekistan on access to financial services and the World Bank’s financial inclusion data to determine the impact and usage of financial services among customers. It is aimed at determining the level of usage of financial services in Uzbekistan by comparing 11 country indicators where surveys were conducted and statistical and SWOT analyses were done. The research on financial inclusion level allowed us to determine the relatively low level of availability of financial and banking services among customers with sufficient cost of financial services as well as suitable and useful information for customers where financial inclusion related to the increase of bank branches and services in rural areas.